Seven ways to get a grip on requests for trigger warnings in medical education - Taylor, Victoria; Hazelton, Lara; Singh, Kathleen (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Trigger warnings are statements provided prior to the delivery of sensitive content that aim to prepare recipients for ensuing distress. In recent years, there have been calls to incorporate trigger warnings into medical education due to the recognition that encountering sensitive content in educational settings can add to the stress experienced by medical students. The evidence for and against their use is inconsistent, and currently there is little consensus on how to, or if we should, introduce trigger warnings into educational settings. In this paper, we present seven ways to get a grip on requests for trigger warnings in medical education: consult your institution; adopt a balanced and evidence-informed approach; encourage self-awareness and help seeking; communicate realistic expectations regarding clinical practice; approach sensitive content as an educational opportunity; foster inclusivity in discussions involving sensitive content; and encourage feedback.